2019
DOI: 10.21608/sjfop.2019.84973
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Plant Growth, Chemical Composition and Secondary Metabolites of Essential Oil of Salt-Stressed Coriander (Coriandrum Sativum L.) Plants Using Selenium, Nano-Selenium, and Glycine Betaine

Abstract: Two pot experiments were carried out under greenhouse conditions during the two successive winter seasons of 2017/2018 and 2018/2019 to enhance the performance of coriander (Coriandrum sativum L.) plants under salt stress conditions (NaCl at 0, 25, 50 and 75 mM). Along with the possibility of enhancing the plant growth, chemical composition, and secondary metabolites of essential oils. Foliar applications of selenium (25 and 50 ppm), nano selenium (25 and 50 ppm), glycine betaine (5 and 10 mM), and distilled w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…In coriander ( Coriandrum sativum L.) plants selenium significantly increased chlorophyll index under salinity stress. In this study, the highest SPAD was recorded with foliar application of 25 ppm selenium [ 44 , 47 ]. One of the strategies of plants in the face of stress is to increase the production of defense compounds such as secondary metabolites [ 13 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In coriander ( Coriandrum sativum L.) plants selenium significantly increased chlorophyll index under salinity stress. In this study, the highest SPAD was recorded with foliar application of 25 ppm selenium [ 44 , 47 ]. One of the strategies of plants in the face of stress is to increase the production of defense compounds such as secondary metabolites [ 13 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…In salinity stressed coriander ( Coriandrum sativum L.) plants, selenium foliar application increased the content of γ-terpinene and geranyl acetate compared with the control. Also, high levels of camphene, γ-terpinene and α-terpinolene, D-limonene, β-citronellol, borneol and geraniol were recorded at 50 ppm selenium application [ 47 ]. In a study conducted by Tavakoli et al [ 51 ] on Melissa officinalis , it was found that the use of 5 μM selenium increased the main constituents of the essential oil, however, the plant is stressed when exposed to high concentrations of selenium.…”
Section: Discussionmentioning
confidence: 99%
“…El-Kinany et al [ 71 ] revealed that applying foliar nSe (25 and 50 mg L −1 ) with the surfactant tween 80 (0.005%) twice every 15 days enhanced yield and ascorbic content in NaCl salt-stressed coriander ( Coriandrum sativum L.) plants. Additionally, Alves et al [ 72 ] observed that when the treatment of 1.0 M of selenite or selenate was added to cadmium (Cd) toxicity (0.5 mM CdCl 2 )-stressed tomato plants, they exhibited an increase in photosynthesis and biomass.…”
Section: Impact Of Se-nps On Growth and Physiologymentioning
confidence: 99%